S21. EEG features in preeclampsia and eclampsia. (May 2018) - Paolini, Stephanie; Waters, Janet; Zaher, Naoir; Urban, Alexandra
Abstract : Introduction: Hypertensive disorders of pregnancy are a global cause of infant and mother mortality. Delivery of the child is the only effective treatment for severe preeclampsia/eclampsia. Currently, we assess central nervous system (CNS) involvement and proceed with pre-term delivery based on patient symptoms, neurologic exam, and, if available, brain imaging. EEG may also be a useful tool in the detection of CNS dysfunction during hypertensive pregnancy. Most studies on this topic were published in the 1950–1960s. Thus, we reviewed recent EEGs obtained in patients with preeclampsia/eclampsia to describe EEG findings and determine if EEG features could predict need for delivery. Methods: The study was approved by the Quality Review Committee. A search of the electronic medical record for "EEG and preeclampsia" and "EEG and eclampsia" (August 2000–August 2017) yielded 40 patients. Patients were included if EEG was performed while they met criteria for severe preeclampsia or eclampsia. Patients were excluded if they had history of seizure disorder, prior known brain pathology, or if their neurologic symptoms/seizure could be attributed to another etiology. Charts and studies were retrospectively reviewed. Fisher's exact test was used to compare normal/abnormal EEG and patient characteristics. Results: Seventeen patients were included. Three patients had preeclampsia and 14 patients had eclampsia. Among initial EEGs, 12 patients (71%) had abnormal EEGs and 5 patients (29%) had normal EEGs. Initial abnormal EEGs were categorized as diffuse slowing (24%), focal slowing (24%), focal sharp waves (12%), seizure activity (12%). Six patients had multiple EEGs: 5 patients demonstrated improvement on subsequent EEGs (correlating to clinical improvement) and 1 patient demonstrated development of sharp waves (in the setting of prolonged hypertension, headache, and abnormal imaging). There were no significant differences in patient symptoms (encephalopathy, vision changes, weakness, sensory changes) or patient prior history (hypertension or preeclampsia/eclampsia) among patients with normal versus abnormal EEGs. Additionally, 14 patients had MRI brain (1 patient with preeclampsia was imaged). There were 3 normal MRIs, 7 MRIs with posterior reversible encephalopathy syndrome, and 4 MRIs with hemorrhage, possible infarct, or seizure related changes. Overall, 16 out of 17 (94%) patients had at least one abnormal study (EEG/MRI). Conclusion: We described patient characteristics, imaging, and EEG features in a small population of patients with severe preeclampsia and eclampsia. Small patient numbers and lack of standard protocol for obtaining EEG in hypertensive pregnancy limit interpretation of results; however, the majority of patients have abnormal EEGs. There must be further study to ascertain the value of routinely using EEG in the evaluation of patients with severe preeclampsia and eclampsia to characterize CNS dysfunction and to predict the need for delivery.